NILAI PENDIDIKAN KARAKTER PADA NOVEL JANSHEN KARYA RISA SARASWATI SERTA RELEVANSINYA DALAM PEMBELAJARAN BAHASA INDONESIA SMA - Wahyu Dini Septiari; Denisa Chotijah Larasati; Andari Saputri (Jurnal Cakrawala Ilmiah, 2022)
Character education is the most important thing in human life to form character for students. The values ​​of character education can be taken through literary works, one of which is novels. This study aims to analyze the values ​​of character education in the novel Janshen by Risa Saraswati and their relevance in learning Indonesian in high school. The research used is a qualitative approach with a descriptive type of research. The data collection technique in this study was using the note-taking technique. The results of this study are the values ​​of character education in the novel Janshen by Risa Saraswati. The values ​​of religious character education are shown in three aspects, namely, obedient to worship, gratitude, and prayer. In addition, there are also educational values ​​for tolerance, creativity, social care, curiosity, discipline, independence, and a love of reading. And it can be relevant as teaching material for Indonesian language education for class XI in accordance with basic competence (KD) 3.20 Analyze the message of the two fiction books (novels and collections of poetry) that are read. Because, the novel contains the values ​​of character education.